Anti‐clockwise rotating shift work and health: Would you prefer 3‐shift or 4‐shift operation?. Issue 5 (17th January 2013) - Mauss, Daniel; Litaker, David; Jarczok, Marc N.; Li, Jian; Bosch, Jos A.; Fischer, Joachim E.
Abstract Background We explored the association between work schedules involving nightshifts and selected measures of health and whether these associations differed among those working in either 3‐ or 4‐shift cycles. Methods Employees at a German industrial company who worked on a fixed daytime schedule or on one involving nightshifts were invited to participate in this cross‐sectional study. Work schedules involving a nightshift were organized into either 3 or 4 shifts rotated anti‐clockwise on a weekly basis. Health characteristics included a range of clinical and physiological measures and self‐reported data on stress and sleep quality. We assessed the independent association of work schedules involving any nightshift and these health characteristics in separate regression analyses, adjusting for age, gender, smoking, and alcohol consumption. Results Nightshift work (N = 133) in general and 3‐shift‐work (N = 53) in particular was associated with decreased sleep quality (P < 0.001). Compared to those working daytime (N = 632), employees working on a 3‐shift cycle had higher adjusted odds of meeting the definition of metabolic syndrome (OR = 2.56 [1.38, 4.75]). Employees working 4‐shift cycles were somewhat less likely to have metabolic syndrome (OR = 1.22 [0.73, 2.05]) and had higher parasympathetic activity measured by heart rate variability (OR = 2.20 [1.04, 4.63]). Conclusions Our data suggest important relationships between shift schedule and a selected group of objective and subjective health measures. Additional research that further clarifies potential mechanisms underlying these relationships is needed. Am. J. Ind. Med. 56:599–608, 2013. © 2013 Wiley Periodicals, Inc.